Endometrial adenocarcinoma with gastrointestinal differentiation – a newly described entity, with morphologic diversity - Stolnicu, Simona; Podoleanu, Cristian; Orban, Ildiko; Francisc, Rozsnyai (Polish Journal of Pathology, 2021)
Gastrointestinal type of endometrial carcinoma is a newly described entity for which clearly defined diagnostic criteria have only recently been published. Among morphologic criteria, gastrointestinal mucinous adenocarcinoma of endometrium must not show a typical endometrioid component. We present a case with morphologic diversity, with areas showing gastric and intestinal differentiation as well as an endometrioid-like component. However, the endometrioid-like component not only did not show classic squamous metaplasia, but was also MUC6-positive, while the positivity for ER/PR was only focal. The recognition of gastric/gastrointestinal differentiation in endometrial carcinomas is best accomplished using both morphology and immunohistochemistry rather than either alone.